Exploring bradyphrenia in Huntington’s disease using the computerized test of information processing (CTiP) - Parkin, Georgia M.; Culbert, Braden; Churchill, Emma; Gilbert, Paul E.; Corey-Bloom, Jody (Clinical parkinsonism & related disorders, 2024)
•The CTiP assesses reaction times for sub-tests of increasing cognitive difficulty.•The CTiP allows for the motor-corrected assessment of cognitive processing.•Intra-individual sub-test differences increase with Huntington’s Disease (HD) stage.•These differences may distinguish HD disease stage or progression.•These findings suggest the presence of bradyphrenia in HD. Bradyphrenia, best thought of as the mental equivalent of bradykinesia, has been described in several disorders of the brain including Parkinson’s disease and schizophrenia; however, little is known about this phenomenon in Huntington’s Disease (HD). The aim of this study was to investigate the presence of bradyphrenia in HD using the Computerized Test of Information Processing (CTiP), an easy to administer and objective task that assesses cognitive processing speed with increasing task complexity. This study included 211 participants: Huntington’s Disease Integrated Staging System (HD-ISS) Stage 0 [n = 28], Stage 1 [n = 30], Stage 2 [n = 48] and Stage 3 [n = 48], and healthy controls (HC) [n = 57]. The CTiP incorporates three subtests: Simple Reaction Time (SRT), which assesses baseline motor function; Choice Reaction Time (CRT), with an added decisional component; and Semantic Search Reaction Time (SSRT), with an added conceptual component. SRT scores were subtracted from CRT and SSRT scores to establish a motor-corrected measure of central conduction time, which was used to operationalize bradyphrenia. HD-ISS and HC within-group reaction times differed significantly when comparing motor-corrected CRT vs SSRT (all ps < 0.0001). Furthermore, the magnitude of these differences increased with HD disease stage (p < 0.0001). An ROC analysis determined that motor-corrected within-subject differences significantly distinguished Stage 2 + 3 from Stage 0 + 1 (AUC = 0.72, p < 0.0001). We report evidence of bradyphrenia in HD that increases with disease progression. This processing deficit, which can be quantified using the CTiP, has the potential to greatly impact HD daily life and warrants additional research.